2016
DOI: 10.1080/00958972.2016.1197391
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, structures and properties of four metal-organic frameworks from chlorophenyl imidazole dicarboxylates

Abstract: Four metal-organic frameworks (MOFs), [Sr(o-ClPhHIDC)have been solvothermally synthesized and structurally characterized. Single-crystal X-ray analyses reveal that 1-3 show two-dimensional architectures and 4 exhibits a three-dimensional structure. The o-ClPhH 3 IDC and m-ClPhH 3 IDC ligands in the polymers can be partly deprotonated and coordinate to metal ions by various modes. The metal ions of 1-4 are coordinated only to oxygens. The thermal and luminescence properties of the polymers have also been invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…As stated in the previous references, , although 1 and 2 first lose lattice water molecules from 72.7 and 22 °C, respectively, the coordinated water molecules still present in the structures below 226.1 °C for 1 and 213 °C for 2 . This means that some of the water molecules can continue to maintain transport of the protons below 100 °C.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…As stated in the previous references, , although 1 and 2 first lose lattice water molecules from 72.7 and 22 °C, respectively, the coordinated water molecules still present in the structures below 226.1 °C for 1 and 213 °C for 2 . This means that some of the water molecules can continue to maintain transport of the protons below 100 °C.…”
supporting
confidence: 61%
“…Although people have researched the proton conductivity of some MOFs constructed by ligands with COOH–, SO 3 H–, or PO 3 H 2 – groups or introduced by protonic guest molecules like imidazole, triazole, histamine, and so on, there is no example concerning imidazole dicarboxylate based MOFs as proton conductors. From previous reports, we found that 1 H -imidazole-4,5-dicarboxylic acid (H 3 IDC) and its 2 position on the imidazole ring-substituted derivatives have indicated outstanding coordination features and various coordination modes. By such ligands as mentioned above, many MOFs with pleasing structures have been built up, but studies on the proton conduction are very scarse. Now considering the promising structural features of imidazole dicarboxylate based MOFs (they contain both imidazole and carboxylate groups, which may be helpful for the proton-conducting pathway), we hope to first explore the proton conductivity of relevant MOFs under different humidities.…”
mentioning
confidence: 99%
See 1 more Smart Citation